Le territoire groenlandais dans la Relation du Groenland de La Peyrère, 1647 - Chevereau, Antoine (Presses universitaires de Rennes, 2019)
Isaac de La Peyrère (1596-1676) is most famous for his Pre-Adamite hypothesis, but he was also an important writer of French knowledge of the North, being the author of a Relation du Groenland and a Relation d’Islande. During a stay in Denmark, he used local archives to compile the first modern study of Greenland, based on medieval Icelandic sagas and recent navigation accounts. Far from the Arctic territory we know, La Peyrère actually depicted a “Green Land,” colonized by Norsemen. Comparing the Saga of Eric the Red to his text, some differences appear; first of all, the French author does not mention the discovery of Vínland, the most important event in Greenlandic sagas. This leads to the hypothesis that Vínland moved to Greenland, an idea which was made possible by the remaining theory of a hyperborean country and a temperate upper-North climate. New descriptions given by whalers exploring the North Atlantic resulted in La Peyrère’s image of the Green Land fading into insignificance in the geography books. Yet there is a point that never disappears about Norse settlements: the idea that they could take advantage of fertile territory in Greenland. Side by side, two images of this arctic island coexist, only separated by a couple of centuries.